Peripheral blood mononuclear cell low molecular mass protein 7 in acute ischemic stroke: vertical change from admission to discharge and correlation with disability, stroke recurrence, and death - Hou, Lujia; Zhang, Yanlei (Frontiers in Immunology, 2024)
Objective: Low molecular mass protein 7 (LMP7) aggravates abnormal T cell differentiation and atherosclerosis, but its clinical role in acute ischemic stroke (AIS) is still unclear. This study aimed to investigate the correlation of peripheral blood mononuclear cell (PBMC) LMP7 with T cell subsets, disease severity, and prognosis in AIS patients. Methods: A total of 162 AIS patients were enrolled for detecting PBMC LMP7 and T helper (Th) 1, Th2, and Th17 cells via reverse transcriptase-polymerase chain reaction and flow cytometry, respectively. Besides, PBMC LMP7 at discharge was also quantified. Results: Increased LMP7 at admission was associated with decreased Th2 cells (P=0.014), and elevated Th17 cells (P<0.001), C-reactive protein (P=0.005), National institutes of health stroke scale (NIHSS) score (P=0.007), and disease severity (defined by NIHSS score) (P=0.010). LMP7 at admission reflected high risk of stroke recurrence (area under curve (AUC): 0.748, 95%confidence interval (CI): 0.564-0.932), but not mRS score at month 3 (M3) >2 (AUC: 0.585, 95%CI: 0.479-0.691) or death (AUC: 0.723, 95%CI: 0.338-1.000). Interestingly, LMP7 at discharge was reduced than that at admission (P<0.001). LMP7 at discharge was positively correlated with the risk of stroke recurrence (AUC: 0.849, 95%CI: 0.735-0.963) and death (AUC: 0.919, 95%CI: 0.836-1.000), but a weak capacity to reflect mRS score at M3 >2 (AUC: 0.671, 95%CI: 0.578-0.765). Conclusion: PBMC LMP7 positively correlates with Th17 cells, inflammation, and disease severity in AIS patients, meanwhile, its level at discharge shows a good ability to reflect the risks of stroke recurrence and death.